2018
DOI: 10.1186/s12955-018-0909-8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between quality of life and physical fitness in people with severe mental illness

Abstract: BackgroundQuality of life of people with severe mental illness may be decrease by the high occurrence of metabolic and cardiovascular diseases. Physical fitness emerges as a modifying factor in this population through physical activity and this modification could influence in the quality of life of this population. The aim of the present study is to determine the contribution of physical fitness to the quality of life of people with severe mental illness.MethodsIn the current study, a physiotherapist and an oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
1
11
0
3
Order By: Relevance
“…4 Department of Physical Medicine and Rehabilitation, Health Sciences / Central Hospital of Central Finland, University of Jyväskylä, Jyväskylä, Finland. 5 Centre for Military Medicine, Helsinki, Finland. 6 Department of biology of Physical Activity, University of Jyväskylä, Jyväskylä, Finland.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Department of Physical Medicine and Rehabilitation, Health Sciences / Central Hospital of Central Finland, University of Jyväskylä, Jyväskylä, Finland. 5 Centre for Military Medicine, Helsinki, Finland. 6 Department of biology of Physical Activity, University of Jyväskylä, Jyväskylä, Finland.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Evidence regarding the relationship between the level of physical fitness and HRQoL, however, is limited. To date, studies related to this topic have most commonly focused on specific target groups with specific health concerns [3][4][5][6] or conditions [7,8] finding a positive relationship between physical fitness and HRQoL. Only few studies have explored this association in the general adult population [9][10][11], but not separately for muscular and cardiorespiratory fitness.…”
Section: Introductionmentioning
confidence: 99%
“…In children and adolescents with type 1 diabetes, Lukács et al [31] examined associations among HRQoL, clinical profiles, anthropometric measures, and physical activity and CRF and found that good CRF was significantly associated with better HRQoL and favorable metabolic control among the youth. Similarly, this positive association between CRF and HRQoL was observed in community-dwelling older adults [32] and workers [33], as well as in patients with CVD [11], McArdle disease [34], severe mental illness [35], and survivors of cancer [36].…”
Section: Discussionmentioning
confidence: 66%
“…Corroborando esta última relação, na tabela 10 e 11 podemos observar que a velocidade de caminhada no primeiro momento (TEMPO CAMINHADA INICIAL) teve relação positiva esperada também em relação à escala UPDRS e a de Fried após 6 meses (0,577 e 0,404, respectivamente). Quanto maior o tempo, ou menor a agilidade para se percorrer determinada distância, mais provável e intensa é a debilidade física esperada destes pacientes, o que relaciona-se com a piora (aumento de pontos) na escala UPDRS e Fried no futuro (Nunes, 2011;Woo et al, 2012;Perez-Cruzado et al, 2018).…”
Section: Procedimentos Do Projetounclassified